PERBEDAAN PEMAHAMAN ELEMEN LAPORAN KEUANGAN ANTARA MAHASISWA YANG MENGACU KURIKULUM INTERNASIONAL DAN KURIKULUM NASIONAL - LINA LINA; BUDI HARTONO KUSUMA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
The study examined the differences of understanding financial statements elements among college students with different high school curriculum background. Data were collected by questionnaires distribution to 189 college students at business school of Pelita Harapan University as respondents. One hundred and fifty eight of 189 question-naires were processed using the Kruskal Wallis H test. The results of this study showed that there are no differences of understanding financial statements elements among college students. Different high school curriculum background did not result the differences of understanding financial statements elements.